SOCIO-GENETIC MOTIVES OF MUI’S FATWA REGARDING COVID-19 BASED ON QURAN-HADITH - Mukhamad Agus Zuhurul Fuqohak; Muh Amiruddin (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2021)
The textual understanding of the Quran and Hadith during the pandemic era has manifested an obstacle for the implementation of the advised health protocols against COVID-19. The textualists try to confront the Quran and Hadith with the social reality of health. They insisted that one should only fear of Almighty God Almighty, not the corona virus, and the congregation of the prayers should be performed at mosques. Against this backdrop, MUI released a guide to worship during the holy month of Ramadan 2020 in the midst of COVID-19. This article, subscribing to qualitative research method investigates the MUI guidance through socio-genetic motive theory. Following the thematic framework, this research found that MUI's socio-genetic motive in appropriating COVID-19 as a mercy (rahmat) is to reduce the potential for conflict, in shifting the meaning of worship to not only in the mosque is to form household harmony, and in optimizing fasting, and zakat is to foster social awareness. While the MUI's motive for basing on Hadith in ordering the use of masks is self-protection and other fellow humans, the motive for maintaining personal hygiene is social health awareness, and the motive to stay at home is not to endanger others. The novelty of this research is to answer the idealism of textualists by combining the study of religious texts with social theory. Keywords: socio-genetic motive; MUI; Quran and Hadith